Molecular- and pollen-based vegetation analysis in lake sediments from central Scandinavia - Parducci, L.; Matetovici, I.; Fontana, S.; Bennett, K.; Suyama, Y.; Haile, James; Kjær, K.; Larsen, N.; Drouzas, A.; Willerslev, E. (John Wiley & Sons Ltd, 2013)
Plant and animal biodiversity can be studied by obtaining DNA directly from the environment. This new approach in combination with the use of generic barcoding primers (metabarcoding) has been suggested as complementary or alternative to traditional biodiversity monitoring in ancient soil sediments. However, the extent to which metabarcoding truly reflects plant composition remains unclear, as does its power to identify species with no pollen or macrofossil evidence. Here, we compared pollen-based and metabarcoding approaches to explore the Holocene plant composition around two lakes in central Scandinavia. At one site, we also compared barcoding results with those obtained in earlier studies with species-specific primers. The pollen analyses revealed a larger numberof taxa (46), of which the majority (78%) was not identified by metabarcoding. The metabarcoding identified 14 taxa (MTUs), but allowed identification to a lower taxonomical level. The combined analyses identified 52 taxa. The barcoding primers may favour amplification of certain taxa, as they did not detect taxa previously identified with species- specific primers. Taphonomy and selectiveness of the primers are likely the major factors influencing these results. We conclude that metabarcoding from lake sediments provides a complementary, but not an alternative, tool to pollen analysis for investigatingpast flora. In the absence of other fossil evidence, metabarcoding gives a local and important signal from the vegetation, but the resulting assemblages show limited capacity to detect all taxa, regardless of their abundance around the lake. We suggest that metabarcoding is followed by pollen analysis and the use of species-specific primers to provide the most comprehensive signal from the environment.